Efektifitas Platform Merdeka Mengajar (PMM) Menggunakan COBIT 2019 Untuk Meningkatkan Kinerja Guru - Mulyadi Tan; Ilivia; Yafri; Aggry Saputra; Larasati Indriastuti (LPPM STMIK Bandung, 2021)
This research is motivated by the need to analyze the capability level and effectiveness of the Merdeka Mengajar Platform (PMM) in enhancing teacher performance using the COBIT 2019 framework. The study aims to assess how well this platform supports the achieve- ment of good IT governance standards and its impact on teaching quality at SMKN 1 Tanjungpinang and SMPIT Taruna Ar Risalah. The research employs both quantitative and qualitative methods with a COBIT 2019 approach, involving domains such as APO07, DSS01, DSS02, MEA01, and BAI03. The results indicate that the effectiveness of PMM usage has reached a fairly good capability level, but there remains a gap between the current capability level (as-is) and the desired level (to-be). The gap values identified are as follows: APO07 (1.2), DSS01 (1.45), DSS02 (1.5), MEA01 (1.25), and BAI02 (1.2). Improvement recommendations are proposed to reduce these gaps and optimize PMM's effectiveness in supporting teacher performance.